2020
DOI: 10.3389/fmicb.2020.00259
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Novel Phages vB_VpS_BA3 and vB_VpS_CA8 for Lysing Vibrio parahaemolyticus

Abstract: Accumulating evidence has indicated that the multiple drug resistant Vibrio parahaemolyticus may pose a serious threat to public health and economic concerns for humans globally. Here, two lytic bacteriophages, namely vB_VpS_BA3 and vB_VpS_CA8, were isolated from sewage collected in Guangzhou, China. Electron microscopy studies revealed both virions taxonomically belonged to the Siphoviridae family with icosahedral head and a long non-contractile tail. The double-stranded DNA genome of phage BA3 was composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 66 publications
2
56
0
Order By: Relevance
“…These morphological characteristics resemble those of the Siphoviridae family. A recent study by Yang et al (2020) reported a similar finding that two V. parahaemolyticus bacteriophages, namely vB_VpS_BA3 and vB_VpS_CA8, isolated from the sewage were Siphoviridae bacteriophage with an icosahedral head (70 × 55 nm) and a long non-contractile tail (125 to 130 nm). Dion et al (2020) reported that double-stranded DNA (dsDNA) tailed bacteriophages accounted for the majority of bacteriophages reported in the public database.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…These morphological characteristics resemble those of the Siphoviridae family. A recent study by Yang et al (2020) reported a similar finding that two V. parahaemolyticus bacteriophages, namely vB_VpS_BA3 and vB_VpS_CA8, isolated from the sewage were Siphoviridae bacteriophage with an icosahedral head (70 × 55 nm) and a long non-contractile tail (125 to 130 nm). Dion et al (2020) reported that double-stranded DNA (dsDNA) tailed bacteriophages accounted for the majority of bacteriophages reported in the public database.…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, Ren et al (2019) reported that a bacteriophage cocktail which consisted of PVP1 and PVP2 bacteriophages was superior in preventing V. parahaemolyticus infections in sea cucumbers than the use of single bacteriophages. It was also recently demonstrated that the benefit of bacteriophage cocktails can help to overcome the development of bacteriophage-resistant pathogen strains (Yang et al, 2020). For instance, Kim et al (2020) demonstrated that a bacteriophage cocktail consists of three types of V. coralliilyticus-specific bacteriophages with greater efficiency against multiple-antibiotic-resistant (MAR) and phage-resistant (PR) V. coralliilyticus infection in oyster larvae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phages against Shigella dysenteriae 2308 were isolated from the New York City sewage by Dubos et al [12]. B_VpS_BA3 and vB_VpS_CA8 phages against Vibrio parahaemolyticus were isolated from sewage collected in China [13]. The vB_KpnP_IME337 phage against carbapenem-resistant Klebsiella pneumoniae was isolated from hospital sewage in China [14].…”
Section: Phages As Pharmaceuticals 21 Phage Isolation and Enrichmentmentioning
confidence: 99%